Analisis Bahaya Serangan Ransomeware Terhadap Layanan Perbankan - Nurul Monika Larasati; Rayyan Firdaus (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
In the ever-growing digital era, banking services also continue to develop and become important for both individuals and businesses to carry out financial transactions quickly and easily. With these technological advances, serious concerns have arisen regarding the security of banking service data. Ransomware is a type of malicious program or malware that threatens to destroy or block access to important data or systems until a ransom is paid by the victim. Ransomware can infect computers in various ways, for example through attached files that the victim downloads, or attacking software directly by looking for vulnerable loopholes. Ransomware attacks have caused many losses, especially in the banking sector, both in terms of financial and customer data security. Protection of banking services from cyber attacks is very important. Proactive prevention efforts, early detection, quick response, application of appropriate technology and implementation of strong data security policies are crucial elements in maintaining the integrity and security of financial transactions. Therefore, it is very important for banking services to understand ransomware attacks and the dangers of ransomware by strengthening computer data security. The research method used is descriptive qualitative research using the literature study method.